Synthesis of bio-derived 1, 4-butanediol by succinic acid esterification and hydrogenation over CuFeAl catalysts. Issue 2 (20th December 2022) - Li, Kefan; Yang, Jiaming; Song, Tongyang; Zhu, Zhirong; Zhao, Chen; Wu, Peng; Li, Xiaohong
Abstract : Synthesis of bio-derived 1, 4-butanediol with a 91.2% yield was realized by succinic acid esterification with methanol over phosphotungstic acid, and then one-pot hydrogenation over a Cu1 Fe1 Al0.5 catalyst in a segmented temperature-controlled manner. Abstract : Sustainability concerns have led to the gradual expansion of the bio-derived 1, 4-butanediol (BDO) monomer market, for the replacement of traditional plastics with biodegradable plastics. Herein, we report a new environmentally friendly route for the synthesis of bio-derived BDO from succinic acid (SA), including the first step of esterification of SA with methanol to yield 100% dimethyl succinate (DMS) over phosphotungstic acid, and the second step of one-pot chemoselective hydrogenation of DMS to BDO with a 91.2% yield over Cu1 Fe1 Al0.5 in a segmented temperature-controlled manner. The method showed excellent long-term stability without deactivation in activity or BDO selectivity during a 500 h time-on-stream test in a fixed-bed reactor. The as-obtained BDO yield with the Cu1 Fe1 Al0.5 catalyst in this case is one of the best results reported so far to the best of our knowledge. It was demonstrated that highly dispersed Cu nanoparticles and relatively higher metallic Cu area, optimal surface Cu 0 /(Cu 0 + Cu + ) molar ratio, and lower surface acidity of the Cu1 Fe1 Al0.5 catalyst were beneficial for the high activities towards the consecutive hydrogenation of DMS to BDO, and moreover, the strong interaction between Cu and Fe or Al species led to the stable performances during the long-term stability test.